Histological findings to five years after early conversion of kidney transplant patients from cyclosporine to everolimus: an analysis from the randomized ZEUS study - Eisenberger, Ute; Sommerer, Claudia (BMC nephrology, 2018)
Conversion from calcineurin inhibitor (CNI) therapy to everolimus within 6 months after kidney transplantation improves long-term graft function but can increase the risk of mild biopsy-proven acute cellular rejection (BPAR). We performed a post-hoc analysis of histological data from a randomized trial in order to further analyze histologic information obtained from indication and protocol biopsies up to 5 years after transplantation.
Gesehen am 13.08.2019